Idiom Bahasa Jepang yang Terbentuk dari Kata Iki: Japanese Idioms Formed from the Word Iki - Syahban Danas; Rani Arfianty (Jurnal Pendidikan Bahasa Jepang Undiksha, 2026)
Abstract Idiom is a phrase whose meaning cannot be understood just by looking at the meanings of the individual words in it. This article discusses the analysis of idioms formed from the word "Iki" in Japanese. The purpose of writing this research is to dig deeper into the understanding of the meaning of idioms in terms of their lexical and idiomatic meanings. The method used in this study is a qualitative descriptive method. The data used in this study are seven idioms formed from the word "Iki." The data source is the Shinkanzen Master vocabulary book for levels N2 and N1. The data collection technique used is library research with note-taking and data analysis techniques presented through descriptive presentation.The results of this study show that idioms formed from the word "Iki" have different meanings and uses depending on the situation and conditions, as well as the phrases that follow them, so that accuracy is needed in communicating both orally and in writing.